Modelling changes in excitability of the peripheral nervous system using compartmentalised microfluidic culture - Rockliffe, Alice (2021)
This thesis describes the use of compartmentalised microfluidic devices to investigate changes in neuronal excitability. All studies carried out in this work were completed in line with principles of the NC3Rs (reduction, replacement and refinement). Particular interest was given to the study of the excitability of dorsal root ganglion neurons (DRGs) in the context of pain-based signalling. This also included the in vitro culture and characterisation of non-neuronal cells involved in inflammation and nociception.